Visitors’ Interaction in an Experiential Designed Environment: A Case Study of a Multimedia Gallery - Elyna Amir Sharji,; Lim Yan Peng,; Peter Charles Woods,; Rose Linda Zainal Abidin, (Wacana Seni Journal of Arts Discourse, 2022)
Currently, there has been a shift in the built environment in creating engaging exhibition spaces such as museums and galleries. This is a challenge nowadays as the creation of digital exhibition spaces depend largely on technological content and devices. Issues arise where visitors may not perceive the intended environment. It is seen that this sense of change needs further study on visitors’ perception and behaviour as users of the space. Experiential design deals with human interaction with the built environment. The objective of this study is to observe how visitors’ behaviour and interaction are influenced by the experiential design concept. A case study is conducted at a local gallery with selected visitor profile of young adults and adults with art and design background. The investigation is done based on the case study guideline, mapping out setting, and timing and tracking observation method to gauge visitors’ perception and action in a multimedia gallery. Eighty visitors were observed throughout the three-day exhibition from 9:00 a.m. to 5:00 p.m. Data collected answers the research question: how does the experiential design concept influence visitors’ behaviour and interaction in a multimedia gallery? The findings are beneficial to understand gallery visitors’ needs in achieving fulfilling interactive and engaging experience. From the observation done, it is identified that multimedia galleries incorporated with experiential design elements build meaningful experiences through the five senses, promotes a sense of place and well-being as well as the allowance for visitors to be more confident in approaching tools and devices that are unfamiliar to them. Curators, designers and artists will gain from this research in designing better interactive environment. The research limitation is the visitor age group which is the young adults and adults’ age group, as well as the single case study done.